Relationship Between Method and Duration of Contraception Usage to Subjective Health Complaints - Nabella Kusuma (Universitas Airlangga, 2016)
Subjective health complaints are symptoms and unpleasant feelings felt by respondents. Health complaints are the biggest cause of acceptors to stop using contraception. The purpose of this study was to look at the relationship between subjective health complaints on family planning acceptors based on contraceptive methods and length of use. This research was an observational analytic study using a cross-sectional design. The study population was contraceptive acceptors living in 6th Sub Village, Kalitengah Sub-District, Sidoarjo District. The sampling technique used in this study is the simple random sampling technique. The independent variables of the study are the type of contraception and the length of use. The statistical test used is the Chi-square test to determine the relationship between variables. The results showed that more respondents were more than 35 years old (62.5%), had senior high school education (59.7%), and were housewives (70.8%). Statistical test with chi-square shows that there is a relationship between contraceptive methods (p = 0.0098) and length of use of contraception (p = 0.012) with subjective health complaints. The hormonal contraceptive method can increase the risk of 4.05 times to experience subjective health complaints compared with respondents who use non-hormonal contraception. Respondents with a duration of contraception ≤ 5 years can increase the risk of 7.82 times to experience subjective health complaints compared with respondents who use contraception for more than 5 years. It was concluded that the method of contraception and the duration of use of contraception was associated with subjective health complaints. It is recommended that midwives educate respondents using hormonal contraception to switch to using non-hormonal contraception when experiencing complaints.